Surface deposition of zinc oxide/vancomycin for enantioselective electrochemical sensing of penicillamine enantiomers - Lim, Alvin Teik Zheng (2018)
The development of chiral electrochemical sensor in the recognition of Penicillamine (Pen) enantiomer is important for the production of pure enantiomers over racemate in the treatment of an array of diseases. The preparation of the modified electrode was a twofold procedure in which electrodeposition of ZnO was conducted first on the ITO glass substrate. The optimum deposition parameters were at –0.9 V, in a buffer solution of pH 7 at 60 oC for 900 s based on the cyclic voltammetry (CV) data obtained. The second part of the procedure involved dropcasting Van solution on the surface of the ZnO/ITO modified electrode. Electrochemical impedance spectroscopy (EIS) were carried out to characterize the electrical conductivity of the modified electrodes.. In this study, a novel chiral electrochemical sensor based on ZnO/vancomycin modified indium tin oxide glass substrate (ZnO/Van/ITO) was successfully fabricated and used in the chiral recognition of Pen enantiomers. The results showed that the charge transfer resistance (RCT) is the greatest for ZnO/Van/ITO followed by ZnO/ITO, Van/ITO and bare ITO. Field Emission Scanning Electron Microscopy was carried out to study the surface morphology of the modified electrodes surface. Different oxidation peak current, Ip of L- and D- Pen were observed in the differential pulse voltammograms (DPV) obtained in the solution containing L- or D-Pen. Under optimum condition, the chiral sensor exhibited good linear response to Pen enantiomers in a linear range of 5 mM to 30 mM with a detection limit of 23.56 mM and 14.73 mM (S/N=3) for the D-Pen and L-Pen respectively. This proposed electrode was shown to exhibit excellent performance in terms of low detection limit and good enantioselectivity for Pen enantiomers. Molecular docking using PyRx was further used to study the computational binding effect of the Van and Pen enantiomers. The results showed that the binding effect was more prevalent for D-Pen as compared to L-Pen with a value of -2.3 kcal/mol and -2.4 kcal/mol for the D-Pen and L-Pen respectively. The association constant from the experiment, KD and KL obtained were 2.314 × 103 and 1.076 ×103 L/mol for the D and L-Pen respectively. The value of KD was larger compared to KL indicating that the binding effect is higher between Van/ZnO with D-Pen. The results obtained suggested that this chiral sensor has the ability to discriminate chiral drugs which is useful in pharmaceutical industries.